Applications of feline immunodeficiency virus as a model to study HIV pathogenesis - Miller, Craig Andrew, author; VandeWoude, Susan, advisor; Hoover, Edward, committee member; Han, Sushan, committee member; Webb, Craig, committee member (Colorado State University. Libraries, 2018)
Feline immunodeficiency virus (FIV) is a naturally-occurring retrovirus that infects domestic and non-domestic feline species, and produces progressive immune depletion that eventually results in an acquired immunodeficiency syndrome (AIDS). While it is accepted that FIV is primarily transmitted by biting, few studies have evaluated FIV oral infection kinetics and transmission mechanisms over the last 20 years. Modern quantitative analyses applied to natural FIV oral infection could significantly further our understanding of lentiviral oral disease and transmission. In this Chapter 1 of this dissertation, I characterized FIV salivary viral kinetics and antibody secretions to more fully document oral viral pathogenesis. The results of this research demonstrate that (i) oral lymphoid tissues serve as a site for enhanced FIV replication, resulting in accumulation of FIV particles and FIV-infected cells in saliva, and (ii) failure to induce a virus-specific oral mucosal antibody response, and/or viral capability to overcome inhibitory components in saliva may perpetuate chronic oral cavity infection. Most importantly, these results provide a model of oral FIV pathogenesis and suggest alternative diagnostic modalities and translational approaches to study oral HIV infection. Feline immunodeficiency virus and human immunodeficiency virus (HIV) utilize parallel modes of receptor-mediated entry. The FIV surface glycoprotein (SU) is an important vaccine target for induction of virus neutralizing antibodies, and autoantibodies to the FIV binding receptor (CD134) block FIV infection ex vivo; highlighting the potential for immunotherapies which utilize anti-receptor antibodies to block viral infection. In Chapter 2 of this dissertation, I immunized cats with soluble CD134, recombinant FIV-SU protein, and/or CD134+SU complexes prior to challenge with FIV to determine if vaccination with CD134-SU complexes could induce protection against FIV infection. Immunization induced production of anti-CD134 and anti-SU antibodies in vaccinated cats, and purified anti-CD134 and anti-SU antibodies significantly inhibited FIV infection in vitro. However, no vaccine combination protected cats from FIV infection in vivo and vaccination induced high titers of antibodies directed at vaccine by-products relative to target antigens. The results of this research reinforce the need to monitor components of vaccine preparations, and emphasize that vaccination may induce proliferation of susceptible target cells and enhancement of heat-labile serum components that counteract neutralizing antibodies. Feline immunodeficiency virus induces lifelong infection in cats and may result in a spectrum of immunodeficiency-related diseases. Both prednisolone and cyclosporine A (CsA) are commonly used clinically to treat lymphoproliferative and immune-mediated diseases in cats, but the impact of these compounds on FIV infection has not been well documented, and their understanding immunomodulatory effects on FIV replication and persistence is critical to guide safe and effective use of these therapies in FIV infected cats. In Chapter 3 of this dissertation, I administered immunosuppressive doses of prednisolone or CsA to cats chronically infected with FIV and monitored alterations in hematological parameters and FIV viral/proviral loads in response to therapy. Interestingly, both treatments caused (i) acute increases in CD4+ lymphocytes, (ii) increased FIV viremia, and (iii) significant alterations in cytokine expression that favored a shift toward a Th2 response. The results of this research highlight the potential for immunosuppressive drug-induced perturbation of FIV replication and underscores the need for consideration of chronic viral infection status when prescribing immunomodulatory medications. Mucosal immune dysfunction, bacterial translocation, systemic immune activation, and chronic inflammation are well-documented features of chronic HIV infection. Despite the success of combinational antiretroviral therapy (cART) in diminishing HIV viral replication and prolonging immune function, a multitude of systemic and local manifestations of HIV infection persist, including the development of chronic inflammation (periodontitis and gingivitis). Commonly used animal models for studying HIV pathogenesis, including SIV/SHIV infections of non-human primates (NHPs) or HIV infections in humanized mice, do not reliably incite oral lesions. In contrast, gingivitis and periodontitis are primary clinical signs associated with untreated natural and experimental FIV-infection, and are principal attributes of this model that may be exploited to investigate pathogenic mechanisms involved in the perturbation of the oral immune system and microbial environment. Therefore, in Chapter 4, I outline the future directions and research goals for my career, and I present preliminary research results obtained thus far in my studies of the pathogenic mechanisms of HIV-induced oral disease. By assessing FIV-associated changes in clinical status, oral microbiota, local and systemic viral burden, and immune profile under such treatment protocols, future studies implementing the feline model of lentiviral-induced oral disease may provide a cornerstone to expand our understanding of the complex interactions between HIV infection, oral immune dysfunction, and the perturbations to the oral microbiota that occur in the context of HIV infection.